Women, urbanization and sustainability : practices of survival, adaptation and resistance - Lacey , Anita (Palgrave Macmillan, 2020)
Contents: Introduction Anita Lacey -- Part I. Contesting livelihoods, land and tenure -- Urban labour and livelihoods: women, postcolonial developmental governance and rapid employment programmes in Honiara and Port Moresby Anita Lacey -- Immanent politics in the Kampungs: gendering, performing and mapping the Jakarta economic subject Lisa Tilley -- Barrio women's gendering practices for sustainable urbanism in Caracas, Venezuela Juan Velasquez Atehortua -- Part II. Resisting water and food insecurity -- Relational trajectories of urban water poverty in Lima and Dar es Salaam Adriana Allen and Pascale Hofmann -- What is being sustained? Sustainability and food exchange sites in Istanbul Candan Turkkan -- Part III. Forging women's rights to the city -- Politics of urban space: rethinking urban inclusion and the right to the city Sudha Mohan -- Disabled women, urbanization, and sustainable development in Africa Tsitsi Chataika -- Fragile cities and gender based violence: the case of Rio de Janeiro Renata A. Giannini, Peter McNamee, and Giovanna B. de Miranda -- Gender justice and the politics of sexual harassment in Cairo Hala Nasr.